E-MODUL SISTEM TRANSMISI OTOMATIS TEKNIK KENDARAAN RINGAN UNTUK SISWA SEKOLAH MENENGAH KEJURUAN - Dela Aprillian Dias Saputra; Suparmin; samsul hadi (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2024)
ABSTRACT Development of e-modules on learning automatic transmission systems. This study aims to: (1) Develop an e-learning module for the automatic transmission system. (2) Knowing the feasibility of the developed automatic transmission system e-module learning media. The development of this learning media e-module uses research development (R&D) and the ADDIE model consisting of (Analysis, Design, Development, Implementation, Evatuation). The subjects in this study consisted of material experts, media experts, and class XI students of the Light Vehicle Engineering Study Program (TKR) at SMK N 1 Nglipar as users of the developed automatic transmission system e-module. The object of this research is shown in the teaching materials. Data collection techniques using a questionnaire (google form questionnaire). The data analysis technique uses quantitative descriptive. The result of this research is an electronic module-based automatic transmission system learning media. The development of the e-module was declared very feasible to use based on the feasibility test according to media experts with a percentage of 81% including the very feasible category and material experts with a percentage of 90% including the very feasible category. The data used for student respondents with a total of 93 people get a percentage of 90% including the very feasible category. Based on the data from the results of the feasibility test, the automatic transmission learning e-module on the Chassis and Power Transfer System material was declared feasible to be used for class XI students of SMK N 1 Nglipar, Gunungkidul. Keywords: E-module Development, Learning Media, Automatic Transmission.